Does consuming more make you happier? Evidence from Chinese panel data - Haining Wang; Zhiming Cheng; Russell Smyth (Bank of Finland, Institute for Economies in Transition (BOFIT), 2015)
This study examines the relationship between consumption and happiness, using panel data from China Family Panel Studies (CFPS). We find that total consumption expenditure has a significant and positive effect on happiness, but we find no evidence of a non-linear relationship between consumption and happiness. There are heterogeneous effects of consumption on happiness across subsamples and for different types of consumption expenditure. We find that relative consumption matters, irrespective if the reference group is de-fined in terms of consumption at the community or county level or on the basis of age, education and gender. However, the extent to which comparison effects are upward looking, or asymmetric, depend on how the comparison group is defined. We also find that comparison with one's past consumption has no significant effect on an individual's happiness.
URN:NBN:fi:bof-201508181355
Keywords: A13; E21; I31; N35; 330